Current, new and novel therapy for castration-resistant prostate cancer. Issue 7 (July 2013) - Gaya, Josep M; Ahallal, Youness; Sanchez-Salas, Rafael; Barret, Eric; Rozet, Francois; Galiano, Marc; Macek, Peter; Durand, Matthieu; Cerruti, Jennifer; Prapotnich, Dominique; Ropert, Stanislas; Bennamoun, Mostefa; et al.
Androgen deprivation therapy is the standard of care for the initial treatment of metastatic prostate cancer. However, the majority of these patients live long enough to experience disease progression despite castration. This scenario is defined as castration-resistant prostate cancer (CRPC) and has a poor outcome and limited options for treatment. First-line treatment after hormonal therapy failure include secondary hormonal manipulation and docetaxel. Advances in the understanding of the molecular mechanisms underlying CRPC have translated into a recent increase in the number of effective systemic agents, and some of them have been already approved as first and second-line treatment. Despite these advances, the median survival in the first-line setting of metastatic CRPC is approximately 20 months and in the postdocetaxel setting is approximately 15 months. Promising and necessary new therapies in Phase III trials include hormonal agents, new cytotoxics agents, as well as other immunotherapeutics and antiprostate-specific membrane antigen therapies.